2020
DOI: 10.32604/biocell.2020.08887
|View full text |Cite
|
Sign up to set email alerts
|

Age-related modifications of macrophages influenced by “inflammageing” in graft vs. host disease

Abstract: Most studies focus on the adaptive immune cells in the GVHD pathogenesis, while little is known about innate immune cells in GVHD occurrence and development, especially macrophages. Meanwhile, a higher incidence of graft versus host disease (GVHD) is also found in the elderly patients. Though advances have been made in the modification of macrophages influenced by the inflamm-ageing, there is still no review on the role of macrophages in GVHD and the association between GVHD and the altered macrophages by infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…NF-κB activation causes the upregulation of inflammatory interleukins and tumor necrosis factor-α (TNF-α) (Tsubaki et al, 2015). The excessive release of inflammatory factors can cause secondary immune injury (Hong et al, 2020). Therefore, this study aimed to investigate the association of TLR3 with RSV induced acute exacerbations of chronic obstructive pulmonary disease (AECOPD).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB activation causes the upregulation of inflammatory interleukins and tumor necrosis factor-α (TNF-α) (Tsubaki et al, 2015). The excessive release of inflammatory factors can cause secondary immune injury (Hong et al, 2020). Therefore, this study aimed to investigate the association of TLR3 with RSV induced acute exacerbations of chronic obstructive pulmonary disease (AECOPD).…”
Section: Introductionmentioning
confidence: 99%
“…In adipose tissue, inflammation inhibits adipocyte expansion and differentiation, alters adipocyte endocrine secretion, and induces extracellular matrix remodelling (Khan et al, 2009). Macrophages play an important role in chronic low-grade inflammation (Hong et al, 2020;Li et al, 2019;Lima et al, 2018). During the development of PCOS, it has been found that hyperandrogenic conditions may lead to the recruitment macrophages under the influence of chemokines (Lima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%